Compact MIMO Slots Antenna Design with Different Bands and High Isolation for 5G Smartphone Applications (Baghdad Science Journal, 2020)
In this paper, two elements of the multi-input multi-output (MIMO) antenna had been used to study the five (3.1-3.55GHz and 3.7-4.2GHz), (3.4-4.7 GHz), (3.4-3.8GHz) and (3.6-4.2GHz) 5G bands of smartphone applications that is to be introduced to the respective US, Korea, (Europe and China) and Japan markets. With a proposed dimension of 26 × 46 × 0.8 mm3, the medium-structured and small-sized MIMO antenna was not only found to have demonstrated a high degree of isolation and efficiency, it had also exhibited a lower level of envelope correlation coefficient and return loss, which are well-suited for the 5G bands application. From the fabrication of an inexpensive FR4 substrate with a 0.8 mm thickness level, a loss tangent of 0.035 and a dielectric constant of 4.3, the proposed MIMO antennas that had been simulated under the five different band coverage were discovered to have demonstrated a respective isolation level of about 14dB, 12dB, 21.5dB, 19dB and 20dB under a -10dB impendence bandwidth. In the measurement and fabrication outcomes that were derived from the use of the prototype MIMO in the (3.4-3.8) band of the Europe and Chinese markets, the proposed MIMO was thus found to have produced a better performance in terms of efficiency, isolation, and envelope correlation coefficient (ECC).